PENGARUH PROFITABILITAS, PERTUMBUHAN PERUSAHAAN, UKURAN PERUSAHAAN DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Wina Ayu Isnaeni; Suryo Budi Santoso; Erny Rachmawati; Selamet Eko Budi Santoso (Review of Applied Accounting Research (RAAR), 2021)
The purpose of this study was to examine the effect of profitability, firm growth, firm size andcapital structure on firm value as proxied by EPS (Earning Per Share) in Islamic commercial bankcompanies registered with OJK for the 2015-2019 period. The independent variables in this studyare profitability, firm growth, firm size and capital structure, while the dependent variable is firmvalue (EPS). The population in this study were Islamic commercial banking companies in the2015-2019 period. The data collection technique used was purposive sampling, in order to obtaina sample of 11 companies with 55 data that matched the criteria. The results of this study showthat profitability has a positive effect on firm value, firm growth does not have a positive effect onfirm value, firm size has a positive effect on firm value, and capital structure has a negative effecton firm value